2019
DOI: 10.1111/ecc.13075
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and breast cancer risk: A qualitative study of women’s perspectives to inform the development of a preventative intervention in breast clinics

Abstract: ObjectiveThis study aimed to explore women's views about breast cancer risk and alcohol use, to inform the design of a prototype for an intervention in breast clinics about alcohol as a modifiable risk factor for breast cancer.MethodsWomen recruited in NHS breast screening and symptomatic clinics in Southampton, UK, were invited to take part in semi‐structured telephone interviews or a focus group to discuss their perspectives of breast cancer risk, alcohol consumption and their information needs about these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Meanwhile, there was lack of perception and awareness among the laywomen about the relationship between alcohol consumption and overweightness or obesity with BC whereas they are of the most consistently reported risk factors in the literature and experts’ opinions. Other qualitative studies on BC risk perception, in line with our results, have revealed that many of the participants considered alcohol irrelevant to BC and this relationship was largely unknown [ 9 , 30 ]. Furthermore, in Iranian studies, the impact of increased body mass index on increasing the risk of BC has been confirmed [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…Meanwhile, there was lack of perception and awareness among the laywomen about the relationship between alcohol consumption and overweightness or obesity with BC whereas they are of the most consistently reported risk factors in the literature and experts’ opinions. Other qualitative studies on BC risk perception, in line with our results, have revealed that many of the participants considered alcohol irrelevant to BC and this relationship was largely unknown [ 9 , 30 ]. Furthermore, in Iranian studies, the impact of increased body mass index on increasing the risk of BC has been confirmed [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…Recently, an effort has been made by public health experts and medical societies to emphasize that reducing alcohol consumption is a vital, and largely neglected, cancer prevention strategy. 28-30 Greater attention to this matter should be given to effectively communicate the role of alcohol as a risk factor for BC and to better investigate its impact on the prevalence of BC in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…This higher female vulnerability appears to be multifactorial and only partly related to the higher blood alcohol levels achieved by women after drinking equivalent amounts of alcohol to men (as confirmed by the results reported in this issue by Dr. Cherpitel and colleagues (2019)). Furthermore, women also are affected by specific alcohol-related consequences, such as the risk of foetal alcohol syndrome in their children if alcohol is consumed during pregnancy (Sokol et al, 2003;Riley et al, 2011) and a dose dependent increased risk of breast cancer, from relatively low levels (10 g/day) of alcohol consumption, of which many women remain unaware (Chambers et al, 2019;Sinclair et al, 2019).…”
mentioning
confidence: 99%